2012
DOI: 10.1016/j.ccr.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Hepatocellular Carcinoma by the Intestinal Microbiota and TLR4

Abstract: SUMMARY Increased translocation of intestinal bacteria is a hallmark of chronic liver disease and contributes to hepatic inflammation and fibrosis. Here we tested the hypothesis that the intestinal microbiota and Toll-like receptors (TLRs) promote hepatocellular carcinoma (HCC), a long-term consequence of chronic liver injury, inflammation and fibrosis. Hepatocarcinogenesis in chronically injured livers depended on the intestinal microbiota, and TLR4 activation in non-bone marrow-derived resident liver cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
1,045
0
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,115 publications
(1,137 citation statements)
references
References 46 publications
32
1,045
0
13
Order By: Relevance
“…The laboratory mouse has been instrumental for establishing roles for the gut microbiota in many aspects of mammalian physiology: angiogenesis (Stappenbeck et al 2002;Reinhardt et al 2012), bone mineral density (Cho et al 2012;Sjö gren et al 2012), brain development and behavior (Sudo et al 2004;Bravo et al 2011;Diaz Heijtz et al 2011;Ezenwa et al 2012), obesity and malnutrition Smith et al 2013), hepatic function (Dapito et al 2012;Henao-Mejia et al 2012), intestinal response to injury and repair (Rakoff-Nahoum et al 2004; Swanson et al 2011), and innate and adaptive immune function (for reviews, see Garrett et al 2010b;Littman and Pamer 2011;Hooper et al 2012). Ninety-nine percent of mouse genes are shared with humans at the host genetic level, and they share key similarities with the human gut microbiome at the phylum through family levels ( Fig.…”
Section: Micementioning
confidence: 99%
“…The laboratory mouse has been instrumental for establishing roles for the gut microbiota in many aspects of mammalian physiology: angiogenesis (Stappenbeck et al 2002;Reinhardt et al 2012), bone mineral density (Cho et al 2012;Sjö gren et al 2012), brain development and behavior (Sudo et al 2004;Bravo et al 2011;Diaz Heijtz et al 2011;Ezenwa et al 2012), obesity and malnutrition Smith et al 2013), hepatic function (Dapito et al 2012;Henao-Mejia et al 2012), intestinal response to injury and repair (Rakoff-Nahoum et al 2004; Swanson et al 2011), and innate and adaptive immune function (for reviews, see Garrett et al 2010b;Littman and Pamer 2011;Hooper et al 2012). Ninety-nine percent of mouse genes are shared with humans at the host genetic level, and they share key similarities with the human gut microbiome at the phylum through family levels ( Fig.…”
Section: Micementioning
confidence: 99%
“…Previous studies have reported pro-tumorigenic effects for different TLRs, such as TLR2 1418 , TLR4 1923 , TLR5 24 , TLR7 10,11,25 and TLR9 2630 . In prostate and breast cancer, the stimulation of TLR9 induced an over-expression of matrix metalloproteinase 13 as well as an increase of cell invasion 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…La translocation de bactéries intestinales est une caractéristique des maladies chroniques hépatiques et contribue à l'inflammation et la fibrose. Le microbiote intestinal et le TLR4, récepteur impliqué dans la reconnaissance des produits bactériens, participent ainsi au développement d'HCC [18]. Un métabolite produit par les bactéries, le propionate, possède en revanche la capacité de réduire la prolifération cellulaire dans le cancer du foie [19].…”
Section: Microbiote Et Immunité Intestinaleunclassified